2022
DOI: 10.1186/s12959-022-00426-7
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of oral anticoagulants in elderly patients with stable coronary artery disease and atrial fibrillation

Abstract: Background This study aimed to evaluate the efficacy and safety of oral anticoagulants (OACs) in real-world elderly patients with comorbidities of stable coronary artery disease (SCAD) and atrial fibrillation (AF). Methods Elderly patients (aged ≥ 65 years old) diagnosed with SCAD and AF were consecutively recruited and grouped into patients with or without oral anticoagulant (OAC) treatment. Follow-up was performed for 5 years. Major adverse cardi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…AF causes various disabling symptoms, including blood pressure drops, palpitations, poor exercise tolerance, and lung congestion ( 4 ). Furthermore, even in the absence of severe coronary artery disease, patients with AF may experience symptoms caused by changes in myocardial perfusion and brief myocardial ischemia such as angina-like chest pain ( 5 , 6 ).…”
Section: Introductionmentioning
confidence: 99%
“…AF causes various disabling symptoms, including blood pressure drops, palpitations, poor exercise tolerance, and lung congestion ( 4 ). Furthermore, even in the absence of severe coronary artery disease, patients with AF may experience symptoms caused by changes in myocardial perfusion and brief myocardial ischemia such as angina-like chest pain ( 5 , 6 ).…”
Section: Introductionmentioning
confidence: 99%
“…Consistent with the result, our study showed the benefits of OAC outweighed an increased risk of fatal side effects in dialysis patients. It is possible that, OAC might have a survival benefit not only through a reduction of thromboembolic risk, but also protecting against myocardial infarction in a considerable number of patients with AF complicated with CAD 22 23. However, OAC treatment did not significantly reduce the risk of 30-day mortality among AKI patients complicated by haemorrhage.…”
Section: Discussionmentioning
confidence: 97%
“…93 The independent net clinical benefit of OACs (and especially of DOACs) has been demonstrated in the elderly patients with stable CAD and AF. 94 However, the need for antiplatelet comedication is being extensively studied so that a particular approach can be reliably established for the elderly AF patients suffering from acute coronary syndrome or undergoing percutaneous coronary intervention (PCI). 95 All the existing trials 96-99 demonstrated that dual therapy (ie, OAC + single antiplatelet treatment, mostly clopidogrel) more significantly reduced the risk of bleeding events than triple therapy (ie, OAC + dual antiplatelet treatment [DAPT]).…”
Section: Peripheral Artery Disease Peripheral Artery Disease (Pad) Is...mentioning
confidence: 99%